Mapping and Interpreting Alternative Economic Experiences in Ecuador: The People's Economy - Tulia Ospina, Ana; Cabezas, Martha; Mármol, David (Whispers from below: Community-based tourism and (other) Ecuadorian initiatives for alternative economies: A closer look, 2026)
This study examines thirteen examples of popular and alternative economies in Ecuador that challenge capitalist logic. The research analyzes how social cooperation and mutual aid emerge as practical mechanisms for survival in the face of adverse conditions. The text proposes a framework for understanding the viability of these associative models, highlighting their ability to foster autonomy and social cohesion without relying on state structures.